Republic of Lithuania : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report examines the Observance of Standards and Codes on Fiscal Transparency for the Republic of Lithuania. Lithuania's fiscal institutional framework meets many requirements of the Code of Good Practices on Fiscal Transparency. Important strengths are clearly defined roles and responsibilities of the three branches of government; limited scope for quasi-fiscal activity at the central government level; and binding debt rules for all levels of government. The reforms that are being implemented promise to ultimately move Lithuania toward best practices in several areas.